PERAN DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL DALAM MENINGKATKAN KEPEMILIKAN AKTA PERKAWINAN MELALUI PROGRAM INOVASI CINTA PANAS DI KABUPATEN SIKKA - Aurelia Kesia Trisnawati; Yustina Olivia da Silva; Maria Modesta Missi Mone (Universitas Nusa Nipa Maumere, 2026)
This study aims to analyze the role of the Population and Civil Registration Office of Sikka Regency in increasing marriage certificate ownership through the Cinta Panas Innovation Program. The research is motivated by the relatively low rate of marriage certificate ownership, which has significant implications for the fulfillment of citizens’ civil rights, particularly in areas facing geographical and socio-cultural barriers. A descriptive qualitative approach was employed, using in-depth interviews, field observations, and document analysis as data collection techniques. Research informants included officials of the Population and Civil Registration Office, village authorities, religious leaders, and community members as service recipients. Data were analyzed interactively through data reduction, data display, and conclusion drawing. The findings indicate that the Cinta Panas Innovation Program has transformed public service delivery from a passive to a proactive approach through outreach services and cross-sector collaboration, especially with religious institutions. The program has improved service accessibility, increased public legal awareness, and contributed to the growth of marriage certificate ownership. Nevertheless, the study also identifies several challenges, including limited institutional capacity, administrative complexity, and unequal program coverage across regions. Therefore, strengthening institutional capacity and ensuring equitable service distribution are essential to sustaining innovation in population administration services